2018
DOI: 10.3389/fmicb.2018.00195
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Activity of a Carbon Monoxide Releasing Molecule (EBOR-CORM-1) Is Shaped by Intraspecific Variation within Pseudomonas aeruginosa Populations

Abstract: Carbon monoxide releasing molecules (CORMs) have been suggested as a new synthetic class of antimicrobials to treat bacterial infections. Here we utilized a novel EBOR-CORM-1 ([NEt4][MnBr2(CO)4]) capable of water-triggered CO-release, and tested its efficacy against a collection of clinical Pseudomonas aeruginosa strains that differ in infection-related virulence traits. We found that while EBOR-CORM-1 was effective in clearing planktonic and biofilm cells of P. aeruginosa strain PAO1 in a concentration depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…For example, Nobre et al reported that the administration of CO gas into the growing cultures could cause significant impairment to the growth of Escherichia coli and Staphylococcus aureus . Recently, CORMs with the capacity of delivering CO directly to intracellular targets have been used as bactericides against a wide range of microorganisms, such as Pseudomonas aeruginosa , Mycobacterium tuberculosis , Helicobacter pylori , pathogenic Escherichia coli , and Neisseria gonorrhoeae . Importantly, CORMs were shown to be more potent bactericides than CO gas due to the accumulation of CORMs inside bacterial cells .…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 99%
“…For example, Nobre et al reported that the administration of CO gas into the growing cultures could cause significant impairment to the growth of Escherichia coli and Staphylococcus aureus . Recently, CORMs with the capacity of delivering CO directly to intracellular targets have been used as bactericides against a wide range of microorganisms, such as Pseudomonas aeruginosa , Mycobacterium tuberculosis , Helicobacter pylori , pathogenic Escherichia coli , and Neisseria gonorrhoeae . Importantly, CORMs were shown to be more potent bactericides than CO gas due to the accumulation of CORMs inside bacterial cells .…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 99%
“…[3] CO is rarely metabolized and is therefore 'stable', reasonably watersoluble and readily traverses cell membranes. CORMs are reported to be effective antibacterial agents, either alone [15][16][17][18][19][20] or in combination with other antibacterial agents. [21][22] The expanding number of new CORMs and their potential have been seen as promising advances, but some recent data cast doubt on the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that CO-RMs are effective at killing or aiding in the killing of P. aeruginosa clinical strains recovered from CF patients and grown in liquid culture or in biofilms (Murray et al, 2012;Flanagan et al, 2018). However, these studies also show that certain P. aeruginosa clinical isolates are less susceptible to CO (Murray et al, 2012;Flanagan et al, 2018). Moreover, the bacterial growth conditions influence CO's effectiveness.…”
Section: The Direct Effects Of Co On Bacteria and Relevance To Cfmentioning
confidence: 98%
“…Along with the previously discussed stimulation of the host cells, CO treatment has an additional potential clinical benefit in its direct bactericidal activity. Multiple studies have documented that CO and CO-RM treatment results in killing of a variety of pathogenic bacteria including P. aeruginosa, E. coli, Salmonella enterica, S. aureus, and Helicobacter pylori (Nobre et al, 2007;Murray et al, 2012;Bang et al, 2014;Rana et al, 2014;Flanagan et al, 2018). This has generally been true regardless of the carrier molecule used to deliver the CO, which accumulates inside bacterial cells before they release CO (Nobre et al, 2016).…”
Section: The Direct Effects Of Co On Bacteria and Relevance To Cfmentioning
confidence: 99%